2022
DOI: 10.1155/2022/8223724
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Collaborative Driving Effect of Artificial Intelligence on Knowledge Innovation Management

Abstract: Artificial intelligence (AI) plays a connotative driving role in cross-border knowledge and factor identification of innovation management. This study explores the collaborative driving effects and influence factors of artificial intelligence on knowledge innovation management. Based on the artificial intelligence application data in knowledge innovation management from 2011 to 2020, this paper adopts the synergy model and the adiabatic elimination to empirically test the influence mechanism and key factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The fourth contribution lies in the exploration of robust empirical validation for the influence of knowledge acquisition and application through the use of AI chatbots like ChatGPT in the workplace. Previous research has suggested that AI can contribute significantly to knowledge management within an organization 102 – 104 , but our study goes a step further by dissecting this effect into the distinct domains of knowledge acquisition and application. Existing literature largely focuses on the general benefits of knowledge acquisition 25 , 105 , 106 and knowledge application 107 109 , but the direct link to utilitarian value and satisfaction in the context of AI chatbots remains underexplored.…”
Section: Discussionmentioning
confidence: 84%
“…The fourth contribution lies in the exploration of robust empirical validation for the influence of knowledge acquisition and application through the use of AI chatbots like ChatGPT in the workplace. Previous research has suggested that AI can contribute significantly to knowledge management within an organization 102 – 104 , but our study goes a step further by dissecting this effect into the distinct domains of knowledge acquisition and application. Existing literature largely focuses on the general benefits of knowledge acquisition 25 , 105 , 106 and knowledge application 107 109 , but the direct link to utilitarian value and satisfaction in the context of AI chatbots remains underexplored.…”
Section: Discussionmentioning
confidence: 84%
“…Publications on this sphere of management indicate both the possibilities for applying AI (e.g., Davenport et al, 2020;Kumar et al, 2019), as well as numerous limitations or even errors in its use (Ascarza et al, 2021;Overgoor et al, 2019). AI is beginning to be used in innovation management (Liu, 2022). It is the result of an innovation process, part of the innovation process, and influences or is influenced by contextual structures (João Correia & Matos, 2021;Navneet et al, 2020).…”
Section: Artificial Intelligence In the 21st Centurymentioning
confidence: 99%